2020
DOI: 10.3390/ijerph17030774
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use, Non-Medical Use of Prescription Drugs, and Depressive Symptoms among Adolescents: A Large-Scale Study in China

Abstract: This large-scale study aimed to test, among Chinese adolescents, the association between problematic Internet use (PIU), non-medical use of prescription drugs (NMUPD), and depressive symptoms, as well as the mediating effects of NMUPD on the associations above. This study used the data from the 2017 National School-based Chinese Adolescents Health Survey, and 24,345 students’ questionnaires qualified for the analyses. Generalized linear mixed models and path models were performed. In the models without mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Large‐scale studies in China (Guo et al, 2018) and Korea (Kwon et al, 2020) have reported that problematic Internet use is associated with an increased risk of suicidal ideation and suicide attempts. The relationship between excessive Internet use and mental health warrants more research (Elhai et al, 2017; Fan et al, 2020). Our findings suggest that young people who spend less time using the Internet may be at lower risk for anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large‐scale studies in China (Guo et al, 2018) and Korea (Kwon et al, 2020) have reported that problematic Internet use is associated with an increased risk of suicidal ideation and suicide attempts. The relationship between excessive Internet use and mental health warrants more research (Elhai et al, 2017; Fan et al, 2020). Our findings suggest that young people who spend less time using the Internet may be at lower risk for anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including unhealthy lifestyle (e.g., lack of exercise or sleep) (Firth et al, 2020), problematic Internet use (Fan et al, 2020), skipping breakfast (Zahedi et al, 2020), life stress related to academic performance (Gao et al, 2020), relationships with teachers (Holdaway & Becker, 2018), parental divorce (D'onofrio & Emery, 2019), only child families (Chi et al, 2020), and traumatic childhood experience(s) (LeMoult et al, 2019), have been associated with mental health among children and adolescents. However, to our knowledge, few studies in China have comprehensively explored these factors in relation to depressive and anxiety symptoms in primary‐to‐high school students.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed that NMUPD can also cause several adverse mental health outcomes, including neurotic, stress-related and somatoform disorders, intimate partner violence and so on [13]. Despite there have been su cient studies demonstrated the association between NMUPD and mental disorders, previous study usually focused on speci ed aspects of EBPs [14] or mainly took opioids misuse [15,16] into consideration. Consequently, it is signi cant to explore the comprehensive association of NMUPD 's effect on EBPs.…”
Section: Introductionmentioning
confidence: 99%
“…İnsan sağlığı açısından bu denli riskleri olan aşırı internet kullanımının, sağlık profesyonelleri ve araştırmacıların ilgi odağı olmasıyla birlikte Problemli İnternet Kullanımı (PİK) kavramı gündeme gelmiştir. PİK' in standart bir tanımı yoktur ve bu nedenle literatürde; internet bağımlılığı, kompulsif kullanım, patolojik internet kullanımı ve yoğun internet kullanımı gibi birçok eşanlamlı terim kullanılır (1)(2)(3). PİK yaygınlığının, ölçüm araçları arasındaki yüksek bir heterojenlik ile dünya genelinde %0,8 ile %26,7 arasında olduğu bildirilmiştir (3,4).…”
Section: Introductionunclassified